MIXING DYNAMICS OF STRATIFIED VORTEX PAST TILTED PIPELINE - YUAN, SHU SHIK (IRC, 2017)
The study of vortex dynamics is an important field in fluid mechanics as vortex has the potential to induce vibration, namely vortex induced vibration (VIV), which can deteriorate the stability and integrity of structures. To prevent accidents due to vortices, a thorough study on vortex physics is necessary. In previous studies, a lot of researches have been conducted on the stratified vortex, through numerical or experimental approaches. However, when comes to a stratified vortex which is formed when a wave past through a tilted pipeline, there is still insufficient study focus on it. The primary objective in this study is to develop a CFD model which simulates the stratified vortex formation when a wave past through a vertical or tilted pipeline in a wave tank, using ANSYS Fluent CFD approach. Also, the effect of tilting this pipeline on the surrounding fluid flow condition and the vortex formation will be investigated. As this study will only focus on the fundamental and theoretical aspects of vortex, application of it in real work will not be included as the scope is limited. A 2D preliminary piston wave tank model is first developed based on Du & Leung (2011) piston wave tank, and is validated against the result in paper. After that, the 2D model is then expanded into 3D model. Further modification is done by inserting pipeline into the model, and changing the water property from single density to stratified condition. The two models developed in the end will be the models having vertical and 5° tilted pipeline, with stratified water in the wave tank. It is found that when a wave past through the pipeline, the velocity contour around the pipeline is highly resembling the initial formation of a von Karman vortex. When tilting the pipeline to right by 5° instead of placing it vertically, the stratified columnar vortex will twist slightly, as compared to the vertical columnar vortex in the vertical pipeline case. Using Reynolds number analysis, the vertical pipeline model is experiencing higher turbulence as compared to the tilted pipeline model, when the similar wave past the pipelines.